Internalization Strategies for Islamic Educational Values Thru Quran Memorization Learning for Students at Junior High School - Husni Laili; Abd Mukti; Asnil Aidah Ritonga (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: Islamic education plays a vital role in shaping students’ character and spirituality, particularly through Tahfiz Quran programs that emphasize not only memorization but also moral and spiritual internalization. This study aims to explore effective strategies for internalizing Islamic values through Quran memorization at three Islamic junior high schools in Deli Serdang. Methodology: This qualitative phenomenological study explores strategies for internalizing Islamic values through Quran memorization at three Islamic junior high schools in Deli Serdang: Junior High School Jabal Noor, Al-Hijrah, and Nurul Ilmi. Data were collected via observation, interviews, and documentation. Main Findings: Islamic values occurs through various strategies, including habituation, exemplary role modeling, talaqqi (direct recitation), muraja’ah (systematic review), reinforcement systems, and active parental involvement. These approaches effectively cultivate students’ faith, worship discipline, morality, and social responsibility in daily life. Supporting factors include teachers’ pedagogical competence, strong religious school culture, and parental collaboration, while challenges arise from limited time, digital distractions, and inconsistent student motivation. Novelty/Originality of this study: This study lies in its integration of classical Tahfiz pedagogy with a modern character education framework, offering a new model for value internalization that harmonizes traditional Islamic learning with contemporary educational demands. This research contributes theoretically by bridging spiritual formation and moral psychology, and practically by proposing a holistic Tahfiz-based model adaptable to modern schooling contexts. The study concludes that Tahfiz Quran, when integrated with reflective understanding, technological awareness, and community engagement, can effectively strengthen Qur’anic character and moral integrity among adolescents in the digital era.